SOME OBSERVATIONS ON SPECIES COMPOSITION AND DETERIORATION OF CROP PLANTATIONS AND FOREST FLORA BY PORCUPINES IN CONSORT WITH CONTROL TECHNIQUES - SARWAR, MUHAMMAD (International Multidisciplinary Research Journal, 2018)
The goal of this article is to inform community regarding porcupines damage, and deliver guidelines for their harmless, real and liable elimination. The utmost apparent attribute of porcupines is their extensive, piercing and shakable quills, which shelter backs of the physiques that make them hit, as a threatening to probable raiders. In general, porcupines occur the maximum in mountainous and gravelly states, however these may adjust in many territories like extremely wet plantations and somewhat territory comprising of prairies, foothills, deserts and tropical forests. Porcupines can become a pest by eating of carrots and other root vegetables, clovers, roots, fruits as well as foraging on the farm crops. A definite indication of porcupine burrow is a mound of feces at entering site of cave or hollow tree. In this global region, Hystrix indica Kerr is most plentiful and scattered species, and has been familiarized as a severe pest of fruit orchards, vegetables, flowering plants, forage grasses in pastures or rangelands and traditional as well as non-traditional crops. When porcupines inflict optimum damage, then their control actions must be adopted. A pest controlling expert can provide skill to recognize the porcupines problematic and decide the superlative promising way out to decide the pest annoyance. Prior to executing a loss managing method, evaluate the porcupines incidence by means of watching for shattered quills, fecal masses beneath nourishing and sleeping plants, or distinctive injury marks to trees in a region. Manipulate habitat to attract more natural predators to control porcupine populations, place aluminum flashing around mature tree trunks and enclose small trees with wire baskets, and enclosure areas with electric or nonelectric fencing, to stop porcupines from gnawing at their bark. Implement forest management practices to reduce food supply and some wood preservatives applied to trees, and use of poison baits may provide partial damage relief. During late spring and summer activity periods, shooting of pest is most effective option, and use steel leg-hold traps lured by salt-soaked ingredients and placing proximate to alive burrows or else frequently used tracks.